Analysis of stool SCFA levels in weaning infants, the timing of weaning, and dietary intake - Leliana, Vidya; Sareharto, Tun Paksi; Pratiwi, Rina (Indonesian Pediatric Society, 2025)
Background Short-chain fatty acids (SCFA) are metabolites of polysaccharides that cannot be digested by microbiota. Differences in SCFA profiles depend on infant diet and intestinal microbiota. The timing of weaning period from breast milk or formula to solid foods affects the transitional microbiome of the gut. Indonesian Pediatric Society recommend the weaning period at at 6 months old. Objective To analyze for differences in stool SCFA levels in weaning infants according to timing of weaning to introductory solid foods and dietary intake. Methods This cross-sectional study was conducted from February to August 2023 in Semarang Primary Health Care Unit. Subjects were infants aged 4-6 months, who underwent fecal SCFA laboratory analysis consisting of acetate, propionic, butyric, and valeric acids, and total SCFA levels, as well as carbohydrate, protein, lipid, and fiber intake assessment through a 3-day food recall processed with Nutrisurvey software of subjects who transitioned to solids before 6 months vs. at 6 months of age. We compared stool SCFA levels in the two groups using T-test analysis. Results Of 50 infants, 23 children (46%) started weaning from breast milk or formula to food at 6 months of age, and 27 children (54%) started weaning before 6 months of age. In this study, there were no significant differences in SCFA levels between those who started at 6 months and before 6 months (P>0.05). There was a weak positive correlation (r = +0.281) between protein intake and propionic acid level (P=0.0481) in all subjects. Conclusion There is no significant difference in SCFA level between starting the weaning period at 6 months and before. However, there is a positive correlation between protein intake and propionic acid, when the analysis was done on all subjects.